2017
DOI: 10.3390/w9090712
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Rainfall-Runoff Events into Nitrate-Nitrogen and Phosphorus Load Assessments for Small Tile-Drained Catchments

Abstract: Rainfall-runoff events significantly influence water runoff and the loss of pollutants from tile-drained agricultural land. We monitored ten small (4 to 38 ha) tile-drained catchments in Czechia for three to five years (2012 to 2016). The discharge was measured continuously; a regular 14-day scheme of water quality monitoring was accompanied with event sampling provided by automatic samplers in 20 to 120 min intervals. A new semi-automated algorithm was developed for the identification of runoff events (RE) ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…The dynamics of drainage runoff and consequently changes of pollutant concentrations and loads are often driven by rainfall-runoff events. During these events, drainage runoff could consist of a large portion of event water, which rapidly infiltrates through polluted topsoil by preferential pathways, and bring this pollution into drainage water (Zajíček et al, 2016;Fučík et al, 2017). Recently, with changes in precipitation distribution during the season, rainfall-runoff events have become an important component of the total runoff.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The dynamics of drainage runoff and consequently changes of pollutant concentrations and loads are often driven by rainfall-runoff events. During these events, drainage runoff could consist of a large portion of event water, which rapidly infiltrates through polluted topsoil by preferential pathways, and bring this pollution into drainage water (Zajíček et al, 2016;Fučík et al, 2017). Recently, with changes in precipitation distribution during the season, rainfall-runoff events have become an important component of the total runoff.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generally, it can be stated that one-function drainage systems (free drainage), besides having the potential to reduce surface runoff and associated soil erosion, also decrease shallow GWL and drain subsurface water from the landscape, even when it is not necessary. The presence of drainage systems generally also deteriorates the quality of related waters, as they carry away dissolved nutrients and other pollutants from the soil by subsurface runoff [54,55].…”
Section: Potential Of Land Drainage Management For Water Balance Improvementmentioning
confidence: 99%
“…Furthermore, a rain gauge and flow meter should also be installed at the sampling site to record the rainfall intensity and runoff volume, respectively. Since it is difficult to collect frequent grab samples, particularly during continuous flows, studies have found this method insufficient to obtain time-weighted average concentrations [57,58]. Automated samplers can ease these drawbacks by taking continuous composite samples with off-site recording of rainfall and runoff flow as well as the date and time of sample collection.…”
Section: Runoffmentioning
confidence: 99%